A pragmatic clinical trial examining the impact of a resilience program on college student mental health. Issue 3 (4th November 2019) - Akeman, Elisabeth; Kirlic, Namik; Clausen, Ashley N.; Cosgrove, Kelly T.; McDermott, Timothy J.; Cromer, Lisa D.; Paulus, Martin P.; Yeh, Hung‐Wen; Aupperle, Robin L.
Abstract: Background: One in three college students experience significant depression or anxiety interfering with daily functioning. Resilience programs that can be administered to all students offer an opportunity for addressing this public health problem. The current study objective was to assess the benefit of a brief, universal resilience program for first‐year college students. Method: First‐year students at a private, midwestern university participated. This trial used a pragmatic design, delivering the intervention within university‐identified orientation courses and was not randomized. The four‐session resilience program included goal‐building, mindfulness, and resilience skills. The comparison was orientation‐as‐usual. Primary outcomes included PROMIS® Depression and Anxiety and Connor‐Davidson Resilience Scale. Secondary and exploratory outcomes included the Perceived Stress Scale, Emotion Regulation, and Cognitive Behavioral Therapy (CBT) Skills Questionnaires, and Freiburg Mindfulness Inventory. Time by treatment interactions at post‐training and semester‐end were examined using linear mixed models. Results: Analysis included 252 students, 126 who completed resilience programming and a matched comparison sample. Resilience programming did not relate to improvements in depression at post‐training (CI: −2.53 to 1.02; p  = .404, d =−0.08), but did at semester‐end (95% CI: −4.27 to −0.72; p  = .006, d  = −0.25) and improvements in perceived stress were observed at post‐training (CI: −3.31 to −0.44; p  = .011, d  = −0.24) and semester‐end (CI: −3.30 to −0.41; p  = .013, d  = −0.24). Emotion regulation, mindfulness, and CBT skills increased, with CBT skills mediating clinical improvements. Conclusions: Universal implementation of a brief, resilience intervention may be effective for improving college student mental health.